Activated neutrophil fluorescent imaging technique for human lungs - Thomas H. Craven (Nature Portfolio, 2021)
Abstract Neutrophil activation is an integral process to acute inflammation and is associated with adverse clinical sequelae. Identification of neutrophil activation in real time in the lungs of patients may permit biological stratification of patients in otherwise heterogenous cohorts typically defined by clinical criteria. No methods for identifying neutrophil activation in real time in the lungs of patients currently exist. We developed a bespoke molecular imaging probe targeting three characteristic signatures of neutrophil activation: pinocytosis, phagosomal alkalinisation, and human neutrophil elastase (HNE) activity. The probe functioned as designed in vitro and ex vivo. We evaluated optical endomicroscopy imaging of neutrophil activity using the probe in real-time at the bedside of healthy volunteers, patients with bronchiectasis, and critically unwell mechanically ventilated patients. We detected a range of imaging responses in vivo reflecting heterogeneity of condition and severity. We corroborated optical signal was due to probe function and neutrophil activation.